INVESTIGATION OF THE DEPENDENCE OF BLADE MICROGEOMETRY ON GRINDING MODES AND CHARACTERISTICS OF THE ABRASIVE TOOL - Saidova Mukhabbat Khamroevna (Journals Park Publishing, 2025)
The formation of a blade occurs due to the intersection of the micro-reliefs of the side surfaces (bevels). The blade microgeometry is influenced not only by the technological parameters of grinding and the physical and mechanical properties of the material, but also by the forces arising during the grinding process and their direction. The significance of various factors characterizing blade formation was evaluated using analysis of variance methods [1].